Faktor – Faktor yang Mempengaruhi Daya Saing Heritage Tourism di Jawa - Edriana Pangestuti (Journal of Tourism Destination and Attraction, 2015)
Indonesia has the potential to further develop as a heritage tourist destination, with many natural and cultural heritage attractions. These heritage tourism advantages could be used as tools to attract tourists and increase the competitive advantage of the destination. This study sought to understand the relationship between destination competitiveness factors (such as the tourist’s image, service quality, satisfaction) and behavioral intention. Little empirical research has explored these relationships from the heritage tourist’s perspective. A mixed method was used to achieve the study’s objectives and test the conceptual model. Twelve in-depth interviews and 400 questionnaire surveys (international and domestic) were conducted using purposive technique sampling. A structural equation modeling (SEM) technique was applied to identify, evaluate and develop the dimensions and test the relationship between these dimensions simultaneously. The final model showed that service quality has a significant relationship with satisfaction but an insignificant relationship with behavioral intention. In addition, this study provided new insights, determining that destination image and service quality factors influence destination competitiveness via the mediating of tourists’ satisfaction in a heritage tourism context. This shows the importance of destination image and service quality for measuring competitiveness. This present model will be useful as a guide for future research for measuring destination competitiveness in the heritage tourism context. Understanding destination competitiveness factors will help marketers predict future travel behavior and develop effective strategies in order to compete with other destinations.